Studi Timbulan, Komposisi dan Potensi Daur Ulang Sampah di Kompleks Perumahan BTN Gemilang 2 Residence - Saputra, Dwi; Ndibale, Wa; Assiddieq, Moch. (Universitas Muhammadiyah Kendari, 2023)
The Watubangga Subdistrict is the second most densely populated area in the Baruga District. However, the sanitation and waste management in the subdistrict are still inadequate. Waste management facilities and waste collection points in the area need to be improved. BTN Gemilang 2 Residence, which is part of the subdistrict, was selected as the research and sampling location. It consists of 62 Type 36 buildings occupied by approximately 162 residents, and it is expected to experience an increase of around 148 residents. This research aims to analyze the generation, composition, and recycling potential of waste in the residential area. Data were obtained through sampling in the residential area, which were then measured and analyzed. The analysis involved sorting the waste into eight components and determining the recyclable waste potential. The research results indicate that the daily waste generation in the residential area amounts to 41.85 kg. Food waste is the most dominant component, followed by hazardous waste, plastic, paper, glass, textiles, and metal. The recycling potential of the waste is estimated to be 57.7% of the total waste generated, consisting of PET and PP plastics, bond paper, glass, metal, and food waste. This research is expected to provide valuable information and data for policy-making and stakeholders involved in waste management in the residential area.